THE EFFECTIVENESS OF INFORMATION SERVICES USING REBT TECHNIQUES TO IMPROVE THE MENTAL HEALTH OF ADOLESCENTS - Lasari, Desy Murni (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2021)
This study aims to describe and test: the mental health condition of students before being given treatment (pretest), mental health conditions of students after being given treatment (post test), the effectiveness of information services with REBT techniques to improve mental health. This research includes quantitative research with experimental methods. Samples were obtained as many as 30 students who were taken through purposive sampling technique. The instrument used is a Likert scale model. While the data analysis technique used is non-parametric statistics, namely Wilcoxon Signed Ranks Test and Kolmogorov Smirnov 2 Independent Samples. The results of this study indicate that there is mental health in the experimental group before and after receiving treatment with information services using the REBT technique. Mental health at the time of the pretest was in the very low category as many as 4 people with a percentage of 13%, 20 students in the low category with a percentage of 67%, 5 students in the high category with a percentage of 16.67%, and 1 student in the very high category with a percentage of 3.33%. After being given treatment there was a change that could be seen from the posttest results as many as 2 students were in the medium category with a percentage of 6.67%, 15 students were in the high category with a percentage of 50% and 13 students were in the very high category with a percentage of 43.33%. . It can be seen from the 30 members of the experimental group who were involved in the calculations, experienced an increase in scores from the pretest and posttest or experienced changes after being provided with information services using the REBT technique.